Finding Fuzzy Critical Path using Revised PILOT Method of Ranking - D. Stephen Dinagar; S. Kamalanathan (International Journal of Mathematics And its Applications, 2017)
In this paper a new ranking method called ``Revised Point of Intersection of Legs of Trapezium (PILOT)'' have been proposed used to find the fuzzy critical path, fuzzy earliest, fuzzy latest times and fuzzy floats in a project management problem. It is quiet interest to study in calculating critical path using generalized trapezoidal fuzzy number. A numerical example is given for justifying the proposed method.